High temperature performance of 316L steel reinforced by particle inoculation and processed by laser powder bed fusion - Adriana Eres-Castellanos; Ana Santana; Luis Miguel Sanz-Moral; Rosalia Rementeria; Rebeca Hernández Pascual; Marta Serrano; Isaac Toda-Caraballo; Jose A. Jimenez; Francisca G. Caballero; Carlos Capdevila (Journal of Materials Research and Technology, 2022)
Grade 316 L is one of the most versatile austenitic stainless-steel products whose potential in laser powder bed fusion has been recently evaluated. A way of improving its properties is to add reinforcements, such as TiC nanoparticles, to promote dispersion hardening. However, it is often difficult to assess microstructure-mechanical property relationships, since particle inoculation promotes heterogeneous nucleation of equiaxed grains during rapid solidification. In this work, two 316 L samples were manufactured by laser powder bed fusion, where the powder of one of them was inoculated with TiC nanoparticles. The effect of inoculants on the microstructure and its high temperature behavior was assessed. Electron Probe Micro Analyzer proved that inoculants did not get dissolved during the printing process and they predominately lay in the intercellular regions, which were solute enriched. Advanced characterization proved that inoculation did not affect the solidification structure, which remained cellular and with a similar size, or the grain size, although it did modify the bulk texture. Finally, the effect of dispersion hardening on the behavior at high temperature of a 316 L steel was evaluated by small punch tests, which proved that the addition of TiC improves all, ductility, yield strength and ultimate tensile strength at high temperature. Moreover, samples processed by LPBF showed high temperature behavior and superior strength and ductility, as compared to the ones obtained in a reference annealed steel, even though the grain size obtained in the former case was at least 50 times larger than the one obtained for the reference condition.